2023
DOI: 10.3390/atmos14040758
|View full text |Cite
|
Sign up to set email alerts
|

Use of Assimilation Analysis in 4D-Var Source Inversion: Observing System Simulation Experiments (OSSEs) with GOSAT Methane and Hemispheric CMAQ

Abstract: We previously introduced the parametric variance Kalman filter (PvKF) assimilation as a cost-efficient system to estimate the dynamics of methane analysis concentrations. As an extension of our development, this study demonstrates the linking of PvKF to a 4D-Var inversion aiming to improve on methane emissions estimation in comparison with the traditional 4D-Var. Using the proposed assimilation–inversion framework, we revisit fundamental assumptions of the perfect and already optimal model state that is typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…A number of studies have demonstrated the effectiveness of adjoint modelling applications such as population-weighted average concertation of pollutants (Koo et al, 2013), premature mortality and health benefits of reducing anthropogenic emissions (Lee et al, 2015;Turner et al, 2015;Pappin and Hakami, 2013a;Pappin et al, 2015 andZhao et al, 2020), nonattainment with the national air quality standards (Hakami et al, 2006;Henze et al, 2009;Pappin and Hakami, 2013b), climate (Lacey et al, 2017;Henze et al, 2012;Karydis et al, 2012;Zhao et al, 2013), crop and vegetation (Lapina et al, 2014, Lyu et al, 2019, economic instruments such as cap and trade program (Mesbah et al, 2012 and and constraining emissions through inverse modelling (Chen et al, 2021;Voshtani et al, 2023).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated the effectiveness of adjoint modelling applications such as population-weighted average concertation of pollutants (Koo et al, 2013), premature mortality and health benefits of reducing anthropogenic emissions (Lee et al, 2015;Turner et al, 2015;Pappin and Hakami, 2013a;Pappin et al, 2015 andZhao et al, 2020), nonattainment with the national air quality standards (Hakami et al, 2006;Henze et al, 2009;Pappin and Hakami, 2013b), climate (Lacey et al, 2017;Henze et al, 2012;Karydis et al, 2012;Zhao et al, 2013), crop and vegetation (Lapina et al, 2014, Lyu et al, 2019, economic instruments such as cap and trade program (Mesbah et al, 2012 and and constraining emissions through inverse modelling (Chen et al, 2021;Voshtani et al, 2023).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%